A territorialidade religiosa pentecostal em São Paulo estudo de caso: Casa Verde Alta - Bonilha, Antônia Rodrigues de Sousa (2009)
This investigation has as central theme neopentecostal the influence of Christianity in shaping the social structure and space of the place where you live who practices in analysis applied to a specific place in the municipality of São Paulo, the subdistrict of Casa Verde Alta, northwest portion of the District the Casa Verde, North of São Paulo. Is inserted in this approach the growth of Pentecostal Protestantism in relation to the hegemony of the Catholic Church, empirically, that sees itself threatened by the growing membership of charismatic believers to dogmas of Pentecostalism. Will be considered, particularly the names and Assembly of God Universal Church of the Kingdom of God